2020
DOI: 10.21608/besps.2019.15104.1030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin and indole-3-carbinol on a rat model of Parkinson’s disease induced by 6-hydroxydopamine

Abstract: Parkinson's disease (PD) is a motor system disorder caused by factors that lead to depletion of dopamine from the dopaminergic neurons in the substantia nigra. Mechanisms of PD include mitochondrial dysfunction, oxidative stress and neuroinflammation. Metformin is an old antidiabetic drug that has recently been shown to offer protective effects against many types of cancer, cardiovascular and neurodegenerative diseases. Indole-3-carbinol (I3C) is a phytochemical derived from the cruciform vegetables. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Further, metformin and I3C combination therapy to 6‐hydroxydopamine (6‐OHDA) induced PD rats substantially ameliorated the oxidative stress, and inflammation (TNF‐α, IL‐6, TGF‐β1, and NF‐kB) and significantly elevated the mitochondrial complex I activity and striated dopamine levels. This research, therefore, demonstrated that metformin and I3C administration together protected rats from 6‐OHDA‐induced PD better than the metformin treatment alone and increased the mitochondrial complex I activity that was decreased in metformin‐treated PD rats (Borg et al, 2020). In vitro, studies revealed that I3C treatment delayed the amyloid beta (Aβ) formation (nucleation and elongation phase) (Morshedi et al, 2007) and inhibited Aβ 1‐140 aggregates and its mediated cytotoxicity (Cohen et al, 2006).…”
Section: Cruciferous Phytochemicals and Their Neuroprotective Activitiesmentioning
confidence: 97%
“…Further, metformin and I3C combination therapy to 6‐hydroxydopamine (6‐OHDA) induced PD rats substantially ameliorated the oxidative stress, and inflammation (TNF‐α, IL‐6, TGF‐β1, and NF‐kB) and significantly elevated the mitochondrial complex I activity and striated dopamine levels. This research, therefore, demonstrated that metformin and I3C administration together protected rats from 6‐OHDA‐induced PD better than the metformin treatment alone and increased the mitochondrial complex I activity that was decreased in metformin‐treated PD rats (Borg et al, 2020). In vitro, studies revealed that I3C treatment delayed the amyloid beta (Aβ) formation (nucleation and elongation phase) (Morshedi et al, 2007) and inhibited Aβ 1‐140 aggregates and its mediated cytotoxicity (Cohen et al, 2006).…”
Section: Cruciferous Phytochemicals and Their Neuroprotective Activitiesmentioning
confidence: 97%
“…13 C NMR (125 MHz, CDCl 3 ):  = 163. 23 50 Synthesized according to the procedure for 3a. Yield: 2.25 g (85%); white solid; mp 86-87 °C.…”
Section: Paper Synthesismentioning
confidence: 99%
“…11 The indole ring is one of the most important structural classes in marketed drugs, such as indomethacin, 12 pravadoline, 13 delavirdine, 14 yohimbine, 15 apaziquone, 16 umifenovir, 17 and panobinostat. 18 In addition, indoles are one of the most important structural motifs among biologically active materials, such as antimicrobial agents, 19 antitumor agents, 20 anticancer agents, 21 antidiabetic agents, 22 anti-Parkinson agents, 23 antiviral agents, 24 anti-inflammatory agents, 25 anti-Alzheimer agents, 26 antibacterial agents, 27 and compounds with analgesic and antioxidant activities. 28 Furthermore, several bioactive indole-based molecules, such as tryptamine, serotonin derivatives, 29 bufotenine, 29a ergot, and vinca alkaloids, 30 have been isolated from plants, fungi, and bacteria.…”
mentioning
confidence: 99%
“…Indoles are promising scaffolds in the medicinal world. Due to versatile applications of natural and synthetic indole derivatives in biological and pharmacological fields, they are being used as drugs, e.g., anti-HIV [4], anticancer [5][6], antimicrobial [7], antioxidant [8][9], anti-inflammatory [10], anticholinesterase [11], antidepressant [12], antihistaminic [13], antiparkinson [14], antitumor [15,16], tubulin inhibitors [17] and receptor inhibitors [18].…”
Section: Applications Of Indole Derivativesmentioning
confidence: 99%